The international barriers to renewable energy development - Kinner, Colter H., author; Daxecker, Ursula, advisor; Saunders, Kyle, advisor; Lacy, Mike, committee member (Colorado State University. Libraries, 2010)
Renewable energy is increasingly seen as a possible solution to problems such as climate change, population growth, economic development, and the limitations of traditional energy sources. Existing research on the international barriers to Renewable Energy Development (RED) is relatively dispersed and has not been subjected to empirical testing. This paper argues that the largest barrier to RED is a lack of enabling policies and regulatory frameworks. Using the degree of state interventionism as a proxy for enabling policies and regulatory frameworks, this paper expects a curvilinear relationship between government ownership of enterprise and RED. A cross national statistical analysis for the 1990-2006 period finds empirical support for many of the proposed barriers to RED. This paper provides researchers and policy makers alike with a better understanding of the international barriers to RED.
Department Head: Robert J. Duffy.